Penggunaan Media Sosial sebagai Sumber Berita oleh Jurnalis Media Daring di Indonesia - Tri Utami Rosemarwati; Lisa Lindawati (Jurnal Studi Komunikasi dan Media, 2019)
Social media content has been widely adopted as a news source and it had become a contemporary phenomenon of journalism all over the globe. Yet, while some academic studies had been undergone in several countries, it remains scarce in Indonesia. Therefore, this study aims to examine Indonesian online journalists’ pattern of using social media as a news source. This pattern is related to how journalists sort and select content in social media along with how they verifiy and build trust over social media content. An offline and online survey were conducted to 77 journalists from 19 Indonesian online media outlets. Findings showed that social media is highly adopted as a news source though majority still used it as secondary source. Interestingly, albeit journalist high adoption of social media as a news source, most of them still hardly trust information they used from social media completely.